Polyphonic Anthropology Theoretical and Empirical Cross-Cultural Fieldwork - Canevacci, Massimo (IntechOpen, 2012)
This book connects anthropology and polyphony: a composition that multiplies the researcher's glance, the style of representation, the narrative presence of subjectivities. Polyphonic anthropology is presenting a complex of bio-physical and psycho-cultural case studies. Digital culture and communication has been transforming traditional way of life, styles of writing, forms of knowledge, the way of working and connecting. Ubiquities, identities, syncretisms are key-words if a researcher wish to interpret and transform a cultural contexts. It is urgent favoring trans-disciplinarity for students, scholars, researchers, professors; any reader of this polyphonic book has to cross philosophy, anatomy, psychology, psychoanalysis, sociology, architecture, archeology, biology. I believe in an anthropological mutation inside any discipline. And I hope this book may face such a challenge.